The Relationship of Maternal Knowledge about Breastfeeding with Exclusive Breastfeeding in Infants Aged 7-12 Months in the Working Area of Puskesmas Balida Dawuan District Majalengka in 2023 - Sri Purwanti, Endah; Mutya Sari, Vianty; Tonasih, Tonasih (Jurnal Medisci, 2024)
Early and exclusive breastfeeding is very important for the survival of a baby, and to protect them from various diseases that they are susceptible to and which can be fatal. The government policy regarding exclusive breastfeeding is regulated in Law Number 36 of 2009 Article 128 paragraphs 2 and 3 which states that during breastfeeding, the family, local government and the community must fully support the mother by providing special time and facilities. The purpose of this study was to determine the relationship between mother's knowledge about breastfeeding and exclusive breastfeeding in the Working Area of ​​the UPTD Balida Health Center, Dawuan District, Majalengka Regency in 2023. This research method is a quantitative study with a descriptive correlation design with a cross sectional approach and probability sampling techniques. sampling with simple random sampling. Respondents in this study amounted to 66 respondents. the results of this study were that the majority of respondents gave exclusive breastfeeding 34 respondents (51.5%), most of the respondents had sufficient knowledge as many as 41 respondents (62.1%) and there was a relationship between mother's knowledge about exclusive breastfeeding with the results of the chi statistical test square with a p value of 0.000 (<0.005). The conclusion in this study is that there is a significant relationship between mother's knowledge about breastfeeding and exclusive breastfeeding.